High prevalence of Duck Hepatitis B virus-associated coinfection in Southwest China. - Xiaoming Lin; Lizhen Gong; Yajia Gou; Yi Liu; Sai Mao; Shun Chen; Mafeng Liu; Dekang Zhu; Mingshu Wang; Renyong Jia; Shaqiu Zhang; Ying Wu; et al. (PLoS ONE)
Currently, five types of duck hepatitis viruses have been documented, and they are all associated with liver disorders. However, the prevalence of their coinfections involving these viruses remains largely uncertain. Herein, we screened the prevalence of the five types of hepatitis viruses from A to E in 143 samples of diseased duck livers during 2019-2021 in Southwest China. We found the highest infection ratio (86.01%, 123/143) of duck hepatitis B virus (DHBV) among all five types of hepatitis viruses. Importantly, a large portion of DHBV-associated coinfections were identified, with 52.85% (65/123) co-infected with Duck Hepatitis A virus (DHAV), 39.84% (49/123) with tentative Duck Hepatitis D virus (DHDV), and 34.96% (43/123) with Duck Hepatitis E virus (DHEV), respectively. Interestingly, a positive correlation between the DHBV-positive rate and the infection rates of the other co-infected hepatitis viruses was revealed, suggesting the importance of DHBV in duck hepatitis virus co-infection events. To understand the situation of bacterial secondary infection, the prevalence of bacterial infection was simultaneously screened using standard 16S rRNA PCR, and hepatitis virus-associated bacterial infections were observed. Collectively, these findings revealed a high prevalence of DHBV-related coinfections and its association with the coinfection of the other duck hepatitis viruses and bacteria. In the future, it is important to study the impact of DHBV co-infection events on disease severity, thereby evaluating the necessity of vaccine development for DHBV.